The maintenance of gender discrimination in the workplace as an institution: Brazilian’s Case Study: El mantenimiento de la discriminación de género en el lugar de trabajo como institución: Estudio de caso brasileño - Gonçalves Moreira, Martiele; Freddo Fleck, Carolina; Almeida Viana, João Garibaldi (Opción, 2025)
The paper aimed to analyze the habits and behaviors that demonstrate and promote discrimination against women in the work environment. As a theoretical lens, we used the Veblenian perspective, which understands that institutions are the way of thinking of men and that individuals have customs, habits, and behaviors that legitimize new institutions or corroborate existing ones. A descriptive-exploratory, qualitative case study analyzed the institution of discrimination against women in the work environment. It was possible to identify that there is a clear definition of the female and male workspace, configuring the sexual division of labor.